Extensão do modelo de onda completa para configurações com múltiplas camadas - Brandão, Diogo Gomes (2020)
This work presents an expansion of the full-wave model to multi-layers. After obtaining the representatives expressions of the magnetic and electric potentials, it is then made calculations of transmission line parameters that describe wave propagation of voltage and currents, for insulated and bare cables, immersed in one out of three possible mediums. Afterwards, the two mediums and three mediums models are compared in order to the new model converge to the pre-existing model under some physical and geometrical configuration. Furthermore, existing models in literature are also used for comparison purposes. This dissertation focus is the study of the described parameters behavior, considering three possible situations of current excitation in the presence of a stratified ground, composed by two layers. The results show that the two-medium model is inappropriate to describe a real physical system. Even in the cases in which the propagation constant of the two-medium model is in close agreement with the one of the new model, there are differences in the characteristic impedance. The convergence of the newly developed model to the pre-established one was achieved. Furthermore, the results indicate that the parameter with greater influence over the propagation characteristics is the resistivity of the ground layers.